Reformas al código de procedimiento penal, sobre la enunciación de la prueba en la sustanciación de las causas penales - PAUTA ALBUJA, VERONICA ALEXANDRA (2010)
The development of this research in the study of the Constitution of the Republic of Ecuador and the Ecuadorian Criminal Procedure Code, regarding the statement of the evidence to be presented at the trial stage. In this study examines the criminal law, and its relevance to the study of crime as a phenomenon and the offender as an active subject of this concept we left the notions of criminal evidence and all its features, principles, evolution, definitions, its importance in that it is essential to a good test for the judge correctly applied the law and criminal law especially when it concerns the fundamental right of a person who is freedom. This research work leads to understand why there must be a single statutory provision governing the listing of criminal evidence, and our legislators know that without a comprehensive understanding of what is criminal procedural law, have imposed a law that be interpreted as making the convenience of both lawyers and the courts.